Análisis del comportamiento del consumidor de los practicantes de artes marciales japonesas de las zonas residenciales de la ciudad de Quito y su impacto en su calidad de vida durante el período 2009-2013 - Villavicencio Campaña, Edison Javier (2015)
Understanding what it means to live for a town with a high quality of life is an investigative task that requires attention to both the objective and subjective scope. The study, performed both a quantitative research to learn what subjective factors that determine the perception that someone has about their good or not quality of life are; taking into account the elements of study are practitioners of Japanese martial arts, a fact which means that the group analyzed intrinsically seeks improved health internal sensations, physical, psychological, power and action being.